XII. studentská vědecká konference Katedry českého jazyka a literatury 8. října 2020 - Oujezdský, Jan (Sborník prací Pedagogické fakulty Masarykovy univerzity, 2020)
Title in English: XII. Student Scientific Conference of the Czech Language and Literature Department. This publication presents papers from an academic conference held in Brno on October 8, 2020. The participants of the conference are Master's and PhD students. Jan Oujezdský focuses on onomastic issues in his paper "Uliční název jako anoikonymum a jeho odlišnosti od ostatních jmen nesídelních objektů [Street Names as Minor Place-names and How they Differ from Other Names of Non-Residential Objects]". Andrea Kytlicová examines spoken expressions in the paper entitled "Větná stavba mluvených projevů žáků 2. stupně ZŠ při komunikaci ve výuce [Sentence Structure of Spoken Expressions of 2nd-grade Elementary School Students in Communication in Teaching]". The paper by Radim Ošmera "Metodologie foneticko-fonologického výzkumu a jeho využití v praxi: Výslovnost hlásky "j" vietnamskými mluvčími [The Methodology of Phonetic-Phonological Research and Its Use in Practice: The Pronunciation of the sound `j' by Vietnamese speakers]", as well as the paper by Lucie Křižková "Pracovní listy k moravským reáliím [Worksheets on Moravian Realities]" are concerned with the problem of teaching students with different mother tongues. Miroslav Jindra's paper "Cestou za zrcadlem: k výzkumu dětského čtenářství žáků třetí třídy základní školy [Through the Looking Glass: Research into the Reading of Third-Grade Primary School Pupils]" is focused on children's reading. The paper by Ondřej Zabloudil Pechník "Tematika přírodních národů v české literatuře devadesátých let dvacátého století [The Themes of Indigenous Peoples in Czech Literature in the 1990s]" concludes the proceedings.